Parenting and families in Australia (Social Policy Research Paper 34) - Jackiewicz, T; Smith, G.J.; Smith, G; Zubrick, S; Sanson, A; Nicholson, J (My University, 2008)
Drawing on data from Wave 1 of the Longitudinal Study of Australian Children, this report discusses specific findings on: parental feeling of stress; sources of social support; parenting styles and family functioning; factors influencing parents' feelings and perceptions about the way they parent their children; the roles and contributions of parents who do not live with their children; and the relationship of parenting practices to child outcomes. The key themes to emerge from the study include: the quality of parenting 'matters' for children, parents feeling that they are doing a good job, the need for continued policy focus on increasing capacity for improved social support, the importance of levels of parent education, and that work is a 'two-edged sword' for parents living in a couples relationship.
Keywords: Families; Families -- Parents and Parenting; Families and relationships; Families; Parents and Parenting; Families and relationships